Literature Review on Medical Incident Command. Issue 2 (9th February 2015) - Rimstad, Rune; Braut, Geir Sverre
Abstract: Introduction: It is not known what constitutes the optimal emergency management system, nor is there a consensus on how effectiveness and efficiency in emergency response should be measured or evaluated. Literature on the role and tasks of commanders in the prehospital emergency services in the setting of mass-casualty incidents has not been summarized and published. Problem: This comprehensive literature review addresses some of the needs for future research in emergency management through three research questions: (1) What are the basic assumptions underlying incident command systems (ICSs)? (2) What are the tasks of ambulance and medical commanders in the field? And (3) How can field commanders' performances be measured and assessed? Methods: A systematic literature search in MEDLINE, PubMed, PsycINFO, Embase, Cochrane Central Register of Controlled Trials, Cochrane Library, ISI Web of Science, Scopus, International Security & Counter Terrorism Reference Center, Current Controlled Trials, and PROSPERO covering January 1, 1990 through March 1, 2014 was conducted. Reference lists of included literature were hand searched. Included papers were analyzed using Framework synthesis. Results: The literature search identified 6, 049 unique records, of which, 76 articles and books where included in qualitative synthesis. Most ICSs are described commonly as hierarchical, bureaucratic, and based on military principles. These assumptions are contested strongly, as is the applicability of such systems. Linking of the chains of command in cooperating agencies is a basic difficulty. Incident command systems are flexible in the sense that the organization may be expanded as needed. Commanders may command by direction, by planning, or by influence. Commanders' tasks may be summarized as: conducting scene assessment, developing an action plan, distributing resources, monitoring operations, and making decisions. There is considerable variation between authors in nomenclature and what tasks are included or highlighted. There are no widely acknowledged measurement tools of commanders' performances, though several performance indicators have been suggested. Conclusion: The competence and experience of the commanders, upon which an efficient ICS has to rely, cannot be compensated significantly by plans and procedures, or even by guidance from superior organizational elements such as coordination centers. This study finds that neither a certain system or structure, or a specific set of plans, are better than others, nor can it conclude what system prerequisites are necessary or sufficient for efficient incident management. Commanders need to be sure about their authority, responsibility, and the functional demands posed upon them. R Rimstad, GS Braut .Literature review on medical incident command .Prehosp Disaster Med .2015 ;30 (2 ):1 -11 .